2013
DOI: 10.1016/j.jedc.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Growth and enduring epidemic diseases

Abstract: This paper studies the formation of human capital and its transmission across generations when premature adult mortality is a salient feature of the demographic landscape, either permanently or in the form of a long-period wave that follows the outbreak of an epidemic. We establish several threshold properties of the model, for such a shock can severely retard economic growth, even to the point of leading to an economic collapse. Premature adult mortality may exacerbate inequality under nuclear family arrangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Moreover, Juhn et al (2013), based on DHS data from all over SSA, concluded that: "Together with the results from other papers that document substantial declines in human capital accumulation, the results here suggest that HIV/AIDS is likely to decrease rather than increase future per capita incomes in Africa" [Juhn et al (2013, p. 851)]. In Bell and Gersbach (2013) and Fink and Linnemayr (2013), the possibility of an economic collapse following the HIV-induced disruption of human capital was further emphasized. Based on a different argument, Ueyama and Yamauchi (2009) found that Malawian women reacted to the HIV risk by lowering the age at marriage.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Moreover, Juhn et al (2013), based on DHS data from all over SSA, concluded that: "Together with the results from other papers that document substantial declines in human capital accumulation, the results here suggest that HIV/AIDS is likely to decrease rather than increase future per capita incomes in Africa" [Juhn et al (2013, p. 851)]. In Bell and Gersbach (2013) and Fink and Linnemayr (2013), the possibility of an economic collapse following the HIV-induced disruption of human capital was further emphasized. Based on a different argument, Ueyama and Yamauchi (2009) found that Malawian women reacted to the HIV risk by lowering the age at marriage.…”
Section: Introductionsupporting
confidence: 68%
“…This hypothesis might become relevant under successful HIV control allowing good health survival of full-blown AIDS individuals. Accounting for heterogeneous agents may allow also capturing the heterogeneity between HIV and AIDS individuals and the issue of HIV-related orphan-hood [Bell and Gersbach (2013)].…”
Section: Implications Of the Results And Further Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Brainerd and Siegler (2003), one of the few on the economic effects of the Spanish influenza, suggests that the 1918-19 pandemic in the US actually increased economic growth in the 1920s. 2 Similarly, using a theoretical economic model, Young (2004) argues that the AIDS epidemic in South Africa will increase net future per capita consumptionwhile Bell and Gersbach (2004) find strong negative effects. Still, studies of the past give us valuable information about the proper assumptions to make when "guesstimating" the macroeconomic impact of future pandemics.…”
Section: Introductionmentioning
confidence: 99%